Effect of Spacing and Nitrogen Fertilizer on Growth, Yield and Quality of Beetroot (Beta vulgaris L.) at Kapilakot, Sindhuli, Nepal - Dhital, Madhav; Sharma, Moha Dutta; Mishra Tripathi, Kalyani; Pande, Keshab Raj; Thapa, Resham Bahadur (Journal of Agriculture and Forestry University, 2025)
A field experiment was conducted at the Horticulture Farm of the College of Natural Resource Management Kapilakot, Sindhuli, Nepal, from October 2020 to January 2021 to determine the spacing and optimum nitrogen fertilizer for the growth, yield, and quality of beetroot variety Madhur. The experiment was laid out in a two factorial RCBD design consisting of 15 treatment combinations replicated three times. The treatment considered three plant spacing (45 cm x 5 cm, 45 cm x 10 cm, and 45 cm x 15 cm) and five doses of N fertilizer (80 kg N ha-1, 100 kg N ha-1, 120 kg N ha-1, 140 kg N ha-1 and 160 kg N ha-1). The results indicated that plant spacing and nitrogen fertilizer doses significantly influenced beetroot growth, yield and quality. The number of leaves per plant (13.37), leaf breadth (11.54 cm), canopy diameter (39.65 cm), root diameter (78.63 mm), root weight plant-1 (186.69 gm), shoot weight plant-1 (156.69 gm), root dry matter (10.56 %), shoot dry matter (9.74 %), TSS (12.67 0Brix) were significantly higher in the wider spacing (45 cm x 15 cm). However, plant height (43.62 cm), leaf length (39.69 cm), root length (11.9 cm), economic yield (40.95 t ha-1) and biological yield (62.95 t ha-1) were significantly higher in close spacing (45 cm x 5 cm). Likewise, plant height (44.2 cm), leaves plant-1 (13.41), leaf length (39.79 cm), root length (12.32 cm), root diameter (72.56 mm), root weight plant-1 (181.32 gm), shoot weight plant-1 (164.43 gm), root dry matter (10.86), shoot dry matter (9.57 %), economic yield (38.14 t ha-1) and biological yield (62.58 t ha-1) were significantly higher in 160 kg N ha-1. However, the canopy diameter (39.12 cm), TSS (13.3 0Brix) and pH (6.6) were significantly higher in plants receiving 120 kg N ha-1. A plant spacing of 45 cm x 5 cm with 160 kg N ha-1 is the best management option for beetroot production in Sindhuli.